2021
DOI: 10.3390/nu13103417
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Metformin Treatment during Gestation and Lactation Improves Skeletal Muscle Development in Offspring of Rat Dams Fed High-Fat Diet

Abstract: Maternal high-fat (HF) diet is associated with offspring metabolic disorder. This study intended to determine whether maternal metformin (MT) administration during gestation and lactation prevents the effect of maternal HF diet on offspring’s skeletal muscle (SM) development and metabolism. Pregnant Sprague-Dawley rats were divided into four groups according to maternal diet {CHOW (11.8% fat) or HF (60% fat)} and MT administration {control (CT) or MT (300 mg/kg/day)} during gestation and lactation: CH-CT, CH-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…A maternal HFD animal model was constructed following standard procedure ( Figure 1 A). Our previous work showed that maternal HFD intake during pregnancy and lactation affects the metabolic phenotype of dams, including higher intake energy, increased adiposity, and higher plasma leptin and insulin concentrations [ 26 , 29 ]. In the current study, we focused on the effects of a maternal HFD on offspring brain development.…”
Section: Resultsmentioning
confidence: 99%
“…A maternal HFD animal model was constructed following standard procedure ( Figure 1 A). Our previous work showed that maternal HFD intake during pregnancy and lactation affects the metabolic phenotype of dams, including higher intake energy, increased adiposity, and higher plasma leptin and insulin concentrations [ 26 , 29 ]. In the current study, we focused on the effects of a maternal HFD on offspring brain development.…”
Section: Resultsmentioning
confidence: 99%
“…Although not statistically significant, metformin seems to counteract the maternal HFD-induced increase in insulin levels in male offspring. Previous studies have also shown that maternal metformin exposure reduces plasma insulin levels in the offspring of obese dams at weaning [ 89 ]. Furthermore, we observed an effect of early metformin exposure on reducing ghrelin levels in both P16 males and females.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, MT increases brain weight as well as total thoracic and abdominal visceral weight in intrauterine growth restriction (IUGR)-affected, small-for-gestational-age (SGA) offspring [72]. Maternal MT treatment during pregnancy and lactation ameliorates the negative effects of a maternal HFD on offspring, and the underlying mechanism may be that MT improves skeletal muscle development through the AMPK/mTOR pathway [73]. In addition, there are sex differences in MT treatment, with females having a smaller body size and males having lower relative weights of major internal organs [74].…”
Section: Metforminmentioning
confidence: 99%